Management of appendiceal mucocele diagnosed intraoperatively - Shekhar, Raj; Singh, Rajendra; Hussain, Syed Nazir; Mayank, Raul; Bharti, Ranvijay (International Surgery Journal, 2019)
Diagnosis of appendiceal mucocele is usually made intraoperatively in emergency operation theatre. It is crucial to recognize and treat this condition appropriately. This study reports management of such cases and their follow up. All cases of appendiceal mucocele diagnosed introperatively in patients undergoing emergency appendectomy at NMCH, Patna over duration of 1 year. Among 210 cases of appendectomy we found two cases of appendiceal mucocele. One patients underwent limited ileocaecal resection and appendectomy was done in the other case. Appendiceal mucocele should be recognized and treated appropriately. Limited ileocaecal resection along with taking care to avoid spillage of contents may suffice at primary surgery. Follow up can be done once histopathological diagnosis and margins are confirmed.